2018
DOI: 10.5539/jas.v10n12p171
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Resistance in F2 Soybean Populations for Adzuki Bean Bruchid (Callosobruchus chinensis)

Abstract: Adzuki bean bruchid (Callosobruchus chinensis) is a significant pest of soybean in Uganda. To sustainably manage this pest, utilization of resistant soybean varieties is the key solution. Development of resistant varieties needs knowledge on modes of inheritance which is crucial in selection of parent materials. To identify parents, a study was initiated to determine the gene action and mode of inheritance of resistance to bruchids in soybean. Nine parental lines were crossed in a full-diallel at Makerere Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The present study detected a total of 13 QTNs using multi-locus GWAS methods. The presence of significant QTNs associated with resistance to bruchids implies the predominance of additive gene action in conditioning soybean resistance to bruchids (10). Previous studies reported the predominance of additive gene action conferring resistance to bruchids in cowpea (11), (38) and common bean (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study detected a total of 13 QTNs using multi-locus GWAS methods. The presence of significant QTNs associated with resistance to bruchids implies the predominance of additive gene action in conditioning soybean resistance to bruchids (10). Previous studies reported the predominance of additive gene action conferring resistance to bruchids in cowpea (11), (38) and common bean (19).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the study carried out by Msiska et al (9) reported that soybean resistance to C. chinensis is due to the overproduction of secondary metabolites such as tannins and the high expression of enzymes such as peroxidases. A further genetic investigation of soybean resistance to C. chinensis revealed that the nature of gene action and mode of inheritance of bruchid resistance traits is quantitative and complex (10). Similarly, quantitative inheritance for resistance to bruchids has been reported in other legumes such as common bean (5) and cowpea (11).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on major leguminous crops have reported the mechanisms of gene actions on the inheritance of resistance. Msiska et al ( 2018 ) observed the existence of additive and non-additive gene factors that influence soybean resistance to C. chinensis . The research also described the maternal effects of the parental genotypes that are core during hybridization.…”
Section: Bruchid Studies In Lablabmentioning
confidence: 99%
“…Varietal resistance to pest attack is the most appropriate method since it is efficient, affects target organisms only, sustainable and reduces the cost of production. Studies on host plant resistance to bruchids have been undertaken in soybean (Msiska 2019), common bean (Maro 2017;Tigist et al 2018), cowpea (Weldekidan 2019), mung bean (L.) R. Wilczek (Somta et al 2006) and pigeon pea (Cajanus cajan L.) Millsp.) (Mishra et al 2019).…”
Section: Host Plant Resistance To Bruchidsmentioning
confidence: 99%
“…This in consequence led to narrowing the genetic base of the Ugandan germplasm, increasing vulnerability to changes in biotic and abiotic stresses (Ssendege et al, 2015;Tukamuhabwa and Oloka, 2016). For instance, the released soybean varieties in Uganda are susceptible to groundnut leaf miner (Namara, 2015;Ibanda et al, 2018) and bruchids (Msiska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%